Da ineficácia da ficção: Fanny Owen, Francisca - Novas Miranda, Rita (Moderna Språk, 2025)
Fanny Owen (1979), by Agustina Bessa-Luís, is a novel in which historiographical, biographical, and literary investigation becomes visible. The work at the boundaries of fiction exposes the investigation, making it, in a way, less effective as fiction. In Manoel de Oliveira’s reading of this novel in Francisca (1981), we observe a similar effect of inefficacy of fiction created through (other) cinematic strategies. Our proposal is to consider how this inefficacy might be a way to think about and reread the novel and a certain romanticism of the 19th century.